2017
DOI: 10.1080/10495398.2017.1329150
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bovine High-Density SNP Genotyping Array in Indigenous Dairy Cattle Breeds

Abstract: In total 52 samples of Sahiwal ( 19 ), Tharparkar ( 17 ), and Gir ( 16 ) were genotyped by using BovineHD SNP chip to analyze minor allele frequency (MAF), genetic diversity, and linkage disequilibrium among these cattle. The common SNPs of BovineHD and 54K SNP Chips were also extracted and evaluated for their performance. Only 40%-50% SNPs of these arrays was found informative for genetic analysis in these cattle breeds. The overall mean of MAF for SNPs of BovineHD SNPChip was 0.248 ± 0.006, 0.241 ± 0.007, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Thus, the highest number of polymorphic markers was observed on chromosome 1: 2252, 2237, 2256 and 2237 in HOL-CHN, HOL-RO, SIM-CHN and SIM-RO, respectively, and the smallest number on chromosome 25: 630, 627, 630 and 626, respectively, followed by chromosomes 27, 28, 29 and 26 (Table 2). Current results are in accordance with the previous studies, where the chromosome 1 had the highest and chromosomes 25-29 the lowest number of filtered SNPs (Zhu et al, 2013;Dash et al, 2017).…”
Section: Resultssupporting
confidence: 93%
“…Thus, the highest number of polymorphic markers was observed on chromosome 1: 2252, 2237, 2256 and 2237 in HOL-CHN, HOL-RO, SIM-CHN and SIM-RO, respectively, and the smallest number on chromosome 25: 630, 627, 630 and 626, respectively, followed by chromosomes 27, 28, 29 and 26 (Table 2). Current results are in accordance with the previous studies, where the chromosome 1 had the highest and chromosomes 25-29 the lowest number of filtered SNPs (Zhu et al, 2013;Dash et al, 2017).…”
Section: Resultssupporting
confidence: 93%
“…The random blood samples were collected from different farms in the country in compliance with the guidelines and regulations of the Institutional Animal Ethics Committee (IAEC), National Bureau of Animal Genetics Resources (ICAR-NBAGR), Karnal (Supplementary Figure S1). After isolation of genomic DNA, estimation of quality and quantity was carried out as described earlier (Dash et al, 2018). DNA samples were genotyped at Sandor Lifesciences Pvt.…”
Section: Animal Resources Snp Genotyping and Quality Controlmentioning
confidence: 99%
“…It has also been indicated that sample size as small as 4 -6 (Willing et al, 2012) and polymorphic SNP filtration (Colli et al, 2018;Utsunomiya et al, 2019) can mitigate ascertainment bias as long as the number of markers is sufficiently large as those under the current investigation. Earlier, in Indian dairy cattle breeds, we also tested bovine high-density genotyping array to assess its feasibility for Zebu cattle genomic studies (Dash et al, 2018). The genome proportion under autozygosity was almost equal in short and long ROH in all the breeds except Vechur.…”
Section: Roh Distribution and Genomic Inbreedingmentioning
confidence: 99%
“…To prepare the dataset we obtained the genotypic data from four high yielding indigenous milch cattle breeds, i.e., Tharparkar (12), Red Sindhi (10), Sahiwal (17) and Gir (24) with two dual-purpose breeds Hariana (10) and Kankrej (10) from Dryad repository (13) data for. ped/.map files accessed via WIDDE (Web-Interfaced next generation database for genetic diversity exploration).…”
Section: Preparation Of Preliminary Datasetmentioning
confidence: 99%
“…Fifty percent of the SNPs of this assortment were found to be informative for genetic analysis of these cattle. The common SNPs with MAF ranging from 0.1 to 0.5 were approximately 50% and 34% for BovineHD and 54K Chips, respectively [10]. In another report, only SNPs in Hardy-Weinberg equilibrium, displaying the highest Minor Allele Frequency across all the thirty populations of French sheep breed (not associated with Mendelian errors in verified family trios) were selected.…”
Section: Introductionmentioning
confidence: 99%